Variations in groundwater discharge and its biogeochemical impact along a precipitation gradient - Waterman, Breanna (Kansas State University, 2020)
Groundwater discharge serves as a link between terrestrial and aquatic habitats that influences stream biogeochemistry, including nutrient availability and system stability. Climate and land use changes can alter the proportion of groundwater discharge in streamflow and impact stream biogeochemistry, but we lack a clear understanding of these relationships. Here, we consider how groundwater discharge varies with land use across Kansas precipitation gradient and the biogeochemical impacts of that variation. To assess proportions of groundwater discharge, we used hydrograph separation to analyze 15 years of continuous streamflow data from 27 streams. The calculation evaluated runoff, baseflow and baseflow index (BFI), which we used as an estimate of groundwater discharge. We evaluated stream biogeochemistry using a grab sampling approach at all sites and used a diel sampling approach at four sites. In addition, we collected groundwater samples at the diel sites. Results show that runoff and baseflow both increase with average annual precipitation (p < 0.001) eastward. However, the eastward increase in runoff is greater than that for baseflow. As such, the average proportion of groundwater discharge in streamflow tends to decrease eastward (p < 0.02). Further, groundwater discharge is influenced by watershed geology, clay content and land use to various degrees. Biogeochemistry results show that variation in major ion concentrations correlate with factors that affect groundwater discharge, such as soil and bedrock properties, as well as land use, and to a lesser extent with the calculated groundwater discharge values. Nutrients (NO₃₋/TN and NPOC) and trace elements (B, V, Ni, Co, Se, Mo, Cd) are more influenced by the proportion of agriculture than the proportion of groundwater discharge. These results highlight the significance of understanding and managing all factors that influence stream biogeochemistry for the future of water resources.
Keywords: Groundwater discharge; Precipitation; Stream biogeochemistry